Heat stress decreased transpiration but increased evapotranspiration in gerbera - Yang, Zaiqiang; Jiang, Yuhan; Qiu, Rangjian; Gong, Xuewen; Agathokleous, Evgenios; Hu, Wei; Clothier, Brent (Frontiers in Plant Science, 2023)
Heat stress is a major constraint for plant production, and evapotranspiration is highly linked to plant production. However, the response mechanism of evapotranspiration to heat stress remains unclear. Here, we investigated the effects of heat stress during two main growth stages on transpiration and evapotranspiration of gerbera. Two levels of day/night temperature were adopted during the vegetative growth stage (VG) and the flowering bud differentiation stage (FBD), namely control (CK; 28/18 ℃) and heat stress (HS; 38/28 °C) levels. The duration of HS was set as 5, 10, 15, and 20 days, respectively. At the beginning of HS, hourly transpiration was mainly inhibited near noon. With continuation of HS, the duration and extent of inhibition of hourly transpiration increased. Daily transpiration rate was also markedly reduced by HS during the VG (18.9%-31.8%) and FBD (12.1%-20.3%) stages compared to CK. The decrease in the daily transpiration rate was greater for longer duration of heat stress. This reduction of transpiration was the main contributor to stomatal limitation at the beginning of HS, while additional inhibition of root activity, leaf area, and root biomass occurred under long-term HS. The daily transpiration rate could not recover after the end of HS (so-called recovery phase), except when HS lasted 5 days during the VG stage. Interestingly, daily evapotranspiration during HS was substantially increased during the VG (12.6%-24.5%) and FBD (8.4%-17.6%) stages as a result of more increased evaporation (100%-115%) than reduced transpiration. However, during the recovery phase, the daily evapotranspiration was markedly decreased at the VG (11.2%-22.7%) and FBD (11.1%-19.2%) stages. Hence, we suggest that disproportionate variation of transpiration and evaporation during HS, especially at the recovery phase, should be considered in various evapotranspiration models and climate scenarios projections.